Makerspaces pedagogy – supports and constraints during 3D design and 3D printing activities in primary schools. Issue 1 (2nd January 2020) - Bower, Matt; Stevenson, Michael; Forbes, Anne; Falloon, Garry; Hatzigianni, Maria
ABSTRACT: Makerspaces have been heralded as an effective way to support the development of 21st Century and STEM capabilities, yet there is a paucity of systematic, multiple-case analysis to guide educator and researcher practice. This collective case study examined 24 primary school classroom contexts to understand what supports and constrains learning and teaching in technology-oriented makerspaces. Thematic analysis of 24 teacher in-situ reflective journals and focus group interviews of all teacher participants revealed 19 supports and 11 constraints, relating to pedagogy, task design, learner attributes, technological factors, the school environment, and teacher capabilities and beliefs. These were used to form an evidence-based framework for learning and teaching in makerspaces. Findings are discussed in relation to previous research which has tended to be anecdotal and based on single cases. Implications for future teaching, research and policy initiatives are also detailed.